NEWSPAPER “NEW DAYS” AS AN TOOL OF THE NATIONAL PROPAGANDA OF THE DIRECTORATE FOR PUBLIC RENEWAL - Mila Krasteva (Издател)
The May 19 coup caused a number of changesin the management of Bulgaria. Until the third decade of the twentieth century, numerous propaganda campaigns were conducted to gain public trust, but the events of May 19, necessitated the establishment of the first centralized Bulgarian propaganda institution – the Directorate for Public Renewal. Among the main tools for legitimizing the new institution is the newspaper “New Days. Morning daily”. Based on a comprehensive overview of the daily, in this article, conclusions are presented about its impact on the readership and the building of a positive image of the Directorate for Public Renewal.